PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. PENJURU WISATA NEGERI - Isdihar, Zavira; Sutoro, Moh. (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of leadership style and work discipline on employee performance at PT Penjuru Wisata Negeri. The method used is quantitative. The sampling technique used saturated sampling and a sample of 32 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, coefficient of determination and hypothesis testing. The results of this research are that Leadership Style (X1) influences employee performance (Y) with a coefficient of determination value of 0.160 or 0.16% and the hypothesis test obtained tcount > ttable (2.391 > 2.045). Work Discipline (X2) has a significant effect on employee performance (Y) with a coefficient of determination value of 0.653 or 65.3% and the hypothesis test obtained tcount > ttable (7.516 > 2.045). Leadership Style (X1) and Work Discipline (X2) have a significant effect on employee performance (Y) with a coefficient of determination value of 0.656 or 65.6% and the hypothesis test obtained tcount > ttable (27.594 > 3.330).